DIAGNÓSTICO E ANÁLISE DA QUALIDADE PERCEBIDA POR ACADÊMICOS DO PROGRAMA DE PÓS - Soares, Julio C. V.; Zeni, Mônica; Dimpério, Maida; Reys, Marcos A. d.; Silveira, Vicente C. P. (Salão do Conhecimento, 2013)
Resumo